2008
DOI: 10.1152/ajpendo.90276.2008
|View full text |Cite
|
Sign up to set email alerts
|

Kinase-specific responsiveness to incremental contractile activity in skeletal muscle with low and high mitochondrial content

Abstract: Ljubicic V, Hood DA. Kinase-specific responsiveness to incremental contractile activity in skeletal muscle with low and high mitochondrial content. Am J Physiol Endocrinol Metab 295: E195-E204, 2008. First published May 20, 2008 doi:10.1152/ajpendo.90276.2008.-Muscle contractions activate protein kinases, leading to signal transduction. We hypothesized that kinase activation would be influenced by mitochondrial content, as well as by contractile activity-induced increases in muscle O 2 consumption (V O2). Kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 81 publications
(119 reference statements)
5
32
0
Order By: Relevance
“…For example, following endurance exercise, the phosphorylation of Akt is immediately increased, but subsequently becomes markedly reduced by 5 h into the recovery phase (43). We also noted this time-dependent phenomenon in other studies (23), and in the current investigation with respect to AMPK phosphorylation 2 h post-contractile activity. In addition, kinase activation is also typically reduced in response to contractile activity if mitochondrial content is elevated (24) within the muscle.…”
Section: Discussionsupporting
confidence: 85%
“…For example, following endurance exercise, the phosphorylation of Akt is immediately increased, but subsequently becomes markedly reduced by 5 h into the recovery phase (43). We also noted this time-dependent phenomenon in other studies (23), and in the current investigation with respect to AMPK phosphorylation 2 h post-contractile activity. In addition, kinase activation is also typically reduced in response to contractile activity if mitochondrial content is elevated (24) within the muscle.…”
Section: Discussionsupporting
confidence: 85%
“…The inability to activate NFjB in response to an acute contraction protocol is associated with severe attenuation of normal changes in expression of cytoprotective genes (36,47,62,76). We have shown that the increases in HSP content and antioxidant enzyme activities stimulated by isometric contractions in muscles of adult rodents were abolished in muscles of old rodents (76).…”
Section: Failure Of Ros-mediated Redox Signaling In Skeletal Muscle Dmentioning
confidence: 92%
“…Immunoblotting-Protein extractions from frozen quadriceps sections were performed as described previously (32). Protein extracts of C2C12 myotubes or muscle homogenates were separated via electrophoresis through SDS-polyacrylamide gels and were then transferred to nitrocellulose membranes (Amersham Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Myotubes-To document the effectiveness of RSV in differentiated muscle cells, we examined the phosphorylation of AMPK and p38 as early indicators of the onset of downstream metabolic effects, as is seen with acute contractile activity (32). Following short term RSV treatment (1 h), AMPK phosphorylation increased by 1.7-fold (p Ͻ 0.05), although p38 phosphorylation was not significantly increased ( Fig.…”
Section: Rsv Induces Ampk and P38 Activity In A Temporal Manner That mentioning
confidence: 99%